(untitled) (Bangladesh Journal of Plant Taxonomy, 2012)
Numerical taxonomy and cladistic analysis of 19 species of Camellia L. were performed using floral morphology containing continuous and discrete units. The current study mostly supports the classifications of 19 species as proposed in previous works. In addition, it also agrees with combining the following species together: C. oleifera and C. vietnamensis; C. sasanqua and C. hiemalis; C. brevistyla and C. puniceiflora; and C. grijsii and C. shensiensis. Further, we propose that C. maliflora be recognized as a variety of C. sasanqua, and C. phaeoclada is best placed in sect. Paracamellia. Moreover, we conclude that these species can be combined: C. tenii and C. miyagii; and C. confusa and C. fluviatilis. Our study indicates that the numerical taxonomy and cladistic analysis based on morphological characters of floral organ is useful in species classification, and this technique appreciated in sect. Oleifera and sect. Paracamellia can be used for identification and classification of other taxa. DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13130 Bangladesh J. Plant Taxon. 19(2): 155-165, 2012 (December)